Influence in everyday life is limited by institutional cultures: A photo elicitation interview study with frail older persons in Swedish residential aged care facilities - Roar Hermansen Østby; Synneve Dahlin-Ivanoff; Sara Hultqvist; David Edvardsson; Qarin Lood (PLoS ONE, 2025)
Earlier studies highlighted the significance of engaging in preferred activities to maintain health and well-being after moving into a residential aged care facility. However, there seem to be significant limitations in the range of activities available, often failing to meet frail older persons’ preferences and needs This raises concerns about the adequacy of opportunities for persons living in residential age care facilities to engage in everyday activities and maintain a sense of purpose and well-being. This study aimed to identify and elucidate frail older persons’ opportunities to influence their everyday life in residential aged care facilities. Thirteen frail older persons living in residential aged care facilities were involved by being asked to take photos of their everyday life over the course of one week. Photo-elicitation interviews were then conducted together with a researcher, to narrate the content and meaning of the photos in relation to opportunities to influence their everyday life. The interviews were analysed using reflexive thematic analysis. The analysis generated one overarching theme: Influence in everyday life is limited by institutional cultures, illustrating how the facilities functioned as institutions that ruled the older persons’ everyday lives. This is further described in two interrelated core themes: 1) A game of power between older persons and staff with the sub-themes Feelings of inferiority and Infringement of integrity, and 2) The importance of dialogue, with the sub-themes The surrounding as a catalyst for the person’s life-story and Becoming part of a community. Institutional cultures were described to affect everything that occurred in the residential aged care facilities, which meant that the older persons’ preferences and needs were not always met. There is a need to further explore the opportunities for persons living in residential aged care facilities to participate in studies on how to attend to their wishes and needs.